The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1111/jocs.13710
|View full text |Cite
|
Sign up to set email alerts
|

Reoperation for composite valve graft failure: Operative results and midterm survival

Abstract: Composite valve graft replacement can be performed with acceptable morbidity and mortality with good mid-term survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Shah et al also illustrated in a series of 15 patients that although in-hospital mortality was only 13%, survival at 12 months remained low at 50% 7. In a recent case series, Maroto et al highlighted that excellent outcomes were achieved at 3 years follow-up (87% survival) in patients who underwent aggressive early surgical intervention with excision and composite graft replacement 5. Some studies have suggested that graft salvage may be successfully achieved with extensive mediastinal debridement, washout with antimicrobial solutions and graft coverage with a vascular tissue flap 11 12…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Shah et al also illustrated in a series of 15 patients that although in-hospital mortality was only 13%, survival at 12 months remained low at 50% 7. In a recent case series, Maroto et al highlighted that excellent outcomes were achieved at 3 years follow-up (87% survival) in patients who underwent aggressive early surgical intervention with excision and composite graft replacement 5. Some studies have suggested that graft salvage may be successfully achieved with extensive mediastinal debridement, washout with antimicrobial solutions and graft coverage with a vascular tissue flap 11 12…”
Section: Discussionmentioning
confidence: 98%
“…Late postoperative infections present non-specifically depending on organism virulence and may include features of endocarditis, aneurysm, fistula formation or subacute infection with systemic features 1 3 4. In those who survive reoperation, 1-year survival ranges between 50% and 87% 2 5. Causative microorganisms are mostly S. aureus, coagulase-negative Staphylococcus, Streptococci and Enterococcus species 1 2 6.…”
Section: Discussionmentioning
confidence: 99%
“…Endovascular technologies are increasingly available to clinicians as options for minimally invasive approaches to complex pathologies [2][3][4][5][6]. While an anastomotic pseudoaneurysm following aortic root replacement is a rare sequela, it poses a challenge given the added morbidity and potential mortality of a reoperative sternotomy [7,8]. The Amplatzer TM Septal Occluder has been previously used in a limited fashion for percutaneous closure of aortic pseudoaneurysms in 13 cases, of whom only two had prior aortic root replacements [5,6].…”
Section: Discussionmentioning
confidence: 99%
“…It may also occur during coronary artery reimplantation in a Bentall procedure. A major indication for a reoperation following the “classic” Bentall procedure were pseudoaneurysms originating from the coronary and distal graft anastomoses . Although the modified Bentall procedure has significantly reduced the incidence of coronary artery complications, late complications may still occur.…”
mentioning
confidence: 99%
“…A major indication for a reoperation following the "classic" Bentall procedure were pseudoaneurysms originating from the coronary and distal graft anastomoses. 3,4 Although the modified Bentall procedure has significantly reduced the incidence of coronary artery complications, 5 late complications may still occur. We present images of a right coronary artery (RCA) occlusion which occurred 10 years following a modified Bentall procedure which resulted in right ventricular dysfunction.…”
mentioning
confidence: 99%